Gases Released During Soil Biodisinfestation of Pepper Greenhouses Reduce Survival of Phytophthora capsici Oospores in Northern Spain - Larregla, Santiago; Gandariasbeitia, Maite; Ojinaga, Mikel; Mendarte, Sorkunde; Guerrero, María del Mar; Ortiz-Barredo, Amaia (Frontiers in Sustainable Food Systems, 2021)
Phytophthora capsici is one of the oomycetes that affects protected pepper crops in different agroclimatic areas of Spain. Currently, environmentally friendly strategies such as biodisinfestation for plant disease control have become increasingly popular. In this study, the effect of released gases during biodisinfestation with a fresh manures mixture amendment on P. capsici oospore viability was determined. A biodisinfestation trial was performed in a greenhouse located in northern Spain (Biscay), with a mixture of fresh sheep (2 kg m−2) and dry poultry manures (0.5 kg m−2) followed by soil sealing with a transparent polyethylene plastic film for 21 days (onset June 15th). Gases were sampled from the aerial cavity of biodisinfested plots at different days after soil sealing (0–1–2–3–4–7–9–11, and 14 days). Vacutainer tubes were incubated at 20°C with oospores of P. capsici that were previously placed under vacuum and refilled with extracted gases. Treatments assayed were gases from different sampling times (0–1–2–3–4–7–9–11–14 days, and succession of days 1–2–3–4–7–9–11–14) combined with different exposure times (7–14–21 days) at 20°C in the laboratory. Control treatments were included: air-tubes and vacuum-tubes. An additional reference treatment under real field conditions was also considered: buried oospores at 15 cm depth in the biodisinfested plots. Oospore viability was determined with the plasmolysis method. The most effective treatment was the succession of gases collected during all sampling days. The significant but slight reduction in oospore viability by exposure to the different gas treatments was consistent with the low dose of applied amendment and the low soil temperature registered at 15 cm depth during soil biodisinfestation (>25°C−100% time, >35°C−23%, >40°C−3%). The above circumstances might have generated a small quantity of gases with low impact on oospore viability. The biodisinfested soil at 15 cm depth reference treatment showed the lowest oospore viability in all the exposure times assayed. The overlap of thermal and higher biofumigation effects in this treatment could likely be responsible for its greater efficacy. A disinfectant effect purely attributable to released gases throughout biodisinfestation has been demonstrated. We believe that our research will serve as a base for future application in agro-environments with reduced thermal inactivation effects.